Accidentally detected nephrocalcinosis in a boy with a homozygous R396W mutation in the CYP24A1 gene – 7-year follow-up - Nowicki, Jakub Krzysztof; Maćkowska, Anna; Rychwalska, Małgorzata; Zaniew, Marcin; Jakubowska-Pietkiewicz, Elżbieta (Pediatria Polska - Polish Journal of Paediatrics, 2023)
Nephrocalcinosis can manifest as frequent urination, haematuria and recurrent urinary tract infections, as well as a decrease in bone mineral density, increasing the risk of osteoporosis. Excessive urinary calcium excretion may have a genetic basis, including mutations within the genes encoding vitamin D3 metabolising enzymes. This paper presents a report of a 7-year follow-up of a boy in whom abdominal ultrasound incidentally detected nephrocalcinosis. The patient was confirmed to have a homozygous R396W mutation in the CYP24A1 gene, which encodes an enzyme responsible for inactivating calcitriol and protecting the cell from vitamin D3 intoxication. Radiological examinations showed a decrease in bone mineral density in the spine. Genetic factors, especially those related to abnormal vitamin D3 metabolism, should be considered in the differential diagnosis of incidentally detected nephrocalcinosis. Children with excessive urinary calcium excretion are at particular risk of developing skeletal complications, including osteopenia and osteoporosis.